Dove Tail Interlocking Tensile Stress Analysis Comparison of ABS and PLA Material in Solid Works Simulation - Bertha Bintari Wahyujati; Felix Krisna Aji (Jurnal POLIMESIN, 2023)
The Tensile Test Method on PLA material for product printing using a 3D printer will recommend the dove tail design as an interlocking part. The result of the design of the dove tail type as an interlocking join part is tested for the most optimal tensile strength. In this paper, consideration for the dove tail design used in material testing and will be printed using a 3D printer is in terms of technical ease of printing and technical testing of its physical form so that it can be gripped using a tensile test tool such as the Universal Tensile Machine (UTM). The dove tail design is designed with a scale representative size that meets the requirements of the standard clamp size of the test tool. Tensile force testing simulation using SolidWorks software will be used as a pre-tensile test analysis before being implemented by UTM. The results obtained are the deformation that is occurring, such as the PLA material having a higher deflection of 7,567 mm and the ABS material having a deflection of 1,897 mm. The strain on interlocking is 0.1081 for ABS material and 0.3988 for PLA material.